Mycobacterium bovis Bacillus Calmette-Guérin-Induced Macrophage Cytotoxicity against Bladder Cancer Cells - Yi Luo; Matthew J. Knudson (Clinical and Developmental Immunology)
Many details of the molecular and cellular mechanisms involved in Mycobacterium bovis bacillus Calmette-Guérin (BCG) immunotherapy of bladder cancer have been discovered in the past decades. However, information on a potential role for macrophage cytotoxicity as an effector mechanism is limited. Macrophages play pivotal roles in the host innate immunity and serve as a first line of defense in mycobacterial infection. In addition to their function as professional antigen-presenting cells, the tumoricidal activity of macrophages has also been studied with considerable interest. Studies have shown that activated macrophages are potent in killing malignant cells of various tissue origins. This review summarizes the current understanding of the BCG-induced macrophage cytotoxicity toward bladder cancer cells with an intention to inspire investigation on this important but underdeveloped research field.